2009
DOI: 10.1080/17290376.2009.9724927
|View full text |Cite
|
Sign up to set email alerts
|

Military men and sexual practices: Discourses of ‘othering’ in safer sex in the light of HIV/AIDS

Abstract: Despite recent reports that there is increasing condom use, generally resistance to condom use is still high. This paper focuses on factors inhibiting condom use and explores issues of responsibility for safe sex practices to prevent infection among a group of 14 South African male soldiers. Military men are particularly vulnerable to HIV because of their working conditions; for example, working far from home and being among communities where they have greater economic and political power, as well as in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…Evidence also suggests that condom use may be considered masculine because it is a signifier of having multiple women sexual partners. Mankayi et al found that South African military men brag about having condoms (131). One man comments: “You know, the more condoms I’ve got in my drawer, the more manly I am.” (p. 36), portraying the idea that condoms represent sexual activity, an important characteristic of masculinity.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also suggests that condom use may be considered masculine because it is a signifier of having multiple women sexual partners. Mankayi et al found that South African military men brag about having condoms (131). One man comments: “You know, the more condoms I’ve got in my drawer, the more manly I am.” (p. 36), portraying the idea that condoms represent sexual activity, an important characteristic of masculinity.…”
Section: Introductionmentioning
confidence: 99%
“…Risk compensation was discussed predominately as something that would happen to ”others”; these others being people in the general community, young people and friends. “Othering” is often achieved through emphasizing difference of demographic characteristics such as race, gender, culture and ethnicity (Mankayi, 2009; Petros, Airhihenbuwa, Simbayi, Ramlagan, & Brown, 2006), and in this case might be a reflection of the data collection methodology: young people were likely not completely comfortable with discussing their own behaviors in a FGD setting. Participants did, however, emphasize the particular vulnerability of their age cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Officers are perceived as being more responsible, therefore taking fewer risks than troops. This suggests that class (status/rank) plays a role in higher-risk sexual practices as during deployment (Mankayi, 2009). Simon expressed his feelings about this practice: 'It's amazing what guys do when they leave their kids and wives at home.…”
Section: Deployment and Higher-risk Sexual Practicesmentioning
confidence: 94%
“…As an example, one participant mentioned that first-year female recruits often have intimate relationships with officers, especially those pursuing their military careers at a tertiary institution. This illustrates how an organisation's hierarchical structures and regular health assessments can foster and exacerbate unsafe sexual practices (for elaboration, see Mankayi, 2009). Hence, understanding the military's structures serves as an indicator of how 'clean' or 'safe' an individual may be deemed to be.…”
Section: Medical Assessment and Higher-risk Sexual Practicesmentioning
confidence: 97%
See 1 more Smart Citation